Algoritmos evolutivos para o problema de seqüenciamento de tarefas em máquinas paralelas com tempos de preparação dependentes da seqüência - Köhler, Viviane Cátia (2004)
This work presents three evolutionary strategies to solve the problem of scheduling a given set of n jobs to m identical parallel machines with the objective of minimizing makespan. There is a sequence dependent setup times. We also compares our method with two other well succeeded heuristics, one is a tabu search based heuristic and the second is a memetic approach, which combines a population-based method with local search procedures. As benchmarks for smallsized instances, optimal values are used provide by a dichotomous search. For larger instances, the comparisons try to show the robust behavior in solution quality as well as in computational effort of our evolutionary strategy.